PERANCANGAN STRATEGI PENINGKATAN KINERJA BAGIAN OPERASI PT. JAYA READYMIX MENGGUNAKAN METODE THEORY OF CONSTRAINT THINKING PROCESS - Anaya Wardhana; Wirendra Satwika Bimantara (Journal of Management and Business Review, 2012)
The main business of PT.Jaya Readymix is supplying readymix concrete to construction projects. The key success factor to win competition in this industry is providing the high quality concrete in competitive price and on-time delivery. To support this key success factor, a company should have good operation performance. The low performance makes the customer dissatisfied and move to other company. When it happens, as the consequence, the revenue of the company will decreas. The indicators of the low performance in the company’s operationis marked with the case of unfinished Corrective Action Report (CAR) in, for example, inability to deliver product on-time and unavailability truck mixer. This research uses the Theory Of Constraint (TOC) Thinking Process to analyze process and to formulate strategy. The steps in this research include identifying and analyzing the core driver of the current company’s problems, and make the action plan to eliminate the problems. All of the process are presented in a form of visual images through a Tree Diagram which is an effect-cause-effect relationship. This research found that the root of the low performance problems of the company's operations is inability of the company to enforce employee discipline. The injected policy to this problem is conducting performance evaluation for plant employees, especially truck drivers, which means it also needs to designed Key Performance Index (KPI) are balanced. In addition, other programs such as procedures socialization, enable the slump stand 2, implementing a new wage system, and implementation of policy briefing before each workshift time is also essential for the company to win competition.